Nanosized ZnGa2O4:Cr3+ Spinets as Highly Luminescent Materials for Bioimaging - Silva, Marlon Nunes da; Carvalho, Jose Miranda de; Abreu Fantini, Marcia Carvalho de; Chiavacci, Leila Aparecida [UNESP]; Bourgaux, Claudie (Amer Chemical Soc, 2019)
In the search for bright probes emitting in the red-to-near-IR region, in the biological transparency window where the absorption and diffusion of light by tissues and the autofluorescence are strongly reduced, Cr3+-doped zinc gallate (ZnGa2O4:Cr3+) spinels have recently attracted much interest because of their persistent luminescence. We present a novel aqueous route for the facile sol-gel synthesis of zinc gallate (ZnGa2O4) and Cr3+-doped zinc gallate nanospinels, with sizes smaller than 150 nm. The synthesis was performed at room temperature, and the obtained nanoparticles were then annealed at moderate temperatures (65, 350, and 700 degrees C). We have characterized the synthesized nanoparticles by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and proton-induced X-ray emission (PIXE). Their optical properties have been investigated. The luminescence of Cr3+ ions, centered at 700 nm, could be excited by wavelengths from UV to visible (250-580 nm). We have highlighted the crucial influence of the zinc gallate host structure on the excitation and emission spectra of Cr3+ ions. After annealing at 700 degrees C, these nanospinels also revealed a persistent luminescence, following an irradiation by UV (290 nm), blue (420 nm), or green-yellow (550 nm) light. UV irradiation was more effective for triggering persistent luminescence, characterized by fast and slow decay mechanisms. The depth of the traps responsible for this persistent luminescence was investigated by thermally stimulated luminescence.
Keywords: ZnGa2O4; ZnGa2O4:Cr-3; new sol-gel synthesis; red-to-near-IR emitting probes; persistent luminescence properties; thermally stimulated luminescence; structure/properties relationship